A Note on Money and the Conduct of Monetary Policy - Jagjit S. Chadha; Luisa Corrado; Sean Holly (University of Kent, School of Economics, 2013)
Prior to the financial crisis mainstream monetary policy practice had become disconnected from money. We outline the basic rationale for this development using a simple model of money and credit in which we explore the conditions under which money matters directly for the conduct of policy. Then, drawing on Goodfriend and McCallum's (2007) DSGE model, we examine the circumstances under which money becomes more closely linked to inflation. We find that money matters when the variance of the supply of lending dominates productivity and the velocity of money demand. This is because amplifying the role of loans supply leads to an expansion in aggregate demand, via a compression of the external finance premium, which is inflationary. We consider a number of alternative monetary policy rules, and find that a rule which exploits the joint information from money and the external finance premium performs best.
Keywords: E31; E40; E51; 330; money; DSGE; policy rules; external finance premium